History of english literature : Traversing the centuries - Aditi Chowdhury; Goswami, Rita (Hyderabad Orient Black Swan, 2019)
A History of English Literature: Traversing the Centuries provides a comprehensive outline of the course of English literature from the Anglo-Saxon period to the present day. In its fourteen chapters, the book covers all major literary periods with inclusive analyses of the political, social and intellectual developments which inevitably contribute to and influence literature in both overt and subtle ways. The survey includes all important literary figures and their significant literary works. The volume is also supplemented with an introductory chapter that discusses the shaping influences on English literature and the royal houses of England. This is followed by a timeline which will enable readers to place each author in the social and political settings and events of the time. In its broad canvass, the book delves into the nuances of everything that goes into the making of English literature. Carefully planned, rich in detail and information, and useful in marking the milestones within various periods as well as drawing the connections between them, A History of English Literature is a reference volume that makes the reading of literary history a stimulating experience for students, scholars and teachers of English literature, and general readers interested in literary history.
Keywords: English Literature History; English Criticism